The Effect of Punishment and Supervision on Work Discipline of Employees of The Cirebon City Regional Secretariat - Salsabila Rizqy Fatihah; Siti Maryam (Rescollacom (Research Collaborations Community), 2026)
This study examines the influence of punishment and supervision on employee work discipline at the Cirebon City Regional Secretariat. Work discipline represents a critical behavioral dimension in public organizations, as it directly relates to compliance with regulations, punctuality, responsibility, and overall organizational effectiveness. Empirical observations indicated persistent disciplinary challenges, including delays in reporting and suboptimal adherence to administrative procedures. A quantitative associative approach was employed to analyze the relationships among variables. Data were collected through questionnaires distributed to 120 employees selected using simple random sampling. Instrument validity and reliability tests confirmed that all measurement items were statistically acceptable. Multiple linear regression analysis was applied to evaluate both partial and simultaneous effects. The results demonstrate that punishment has a positive and significant effect on work discipline, indicating that firm, fair, and consistent sanctions contribute to improved employee compliance and responsibility. Supervision also shows a positive and significant effect, suggesting that continuous monitoring and evaluation reinforce disciplined work behavior. Simultaneously, punishment and supervision significantly influence work discipline, highlighting their complementary roles as corrective and preventive managerial mechanisms. The coefficient of determination reveals that both variables explain a substantial proportion of discipline variation. These findings emphasize the importance of strengthening sanction policies and supervisory practices to enhance employee discipline in public sector organizations.